Ionic liquid brush as an efficient and reusable heterogeneous catalytic assembly for the tosylation of phenols and alcohols in neat water. (22nd May 2017) - Feng, Simin; Li, Jing; Wei, Junfa
Abstract : An efficient and reusable heterogeneous catalytic assembly-ionic liquid brush was developed for tosylation of phenols and alcohols in neat water. Abstract : A very efficient and reusable heterogeneous ionic liquid brush assembly was developed. The catalyst exhibits high catalytic activity for the tosylation of phenols and alcohols in neat water. Moreover, the catalyst shows outstanding stability and reusability, and it can be simply and effectively recovered and reused five times without noticeable loss of catalytic activity.